The Use of Digital Technology in The Optimization of Modern Industrial Supply Chain Management: A Systematic Literature Review - Dwi Nurfitrianto; Rida Zuraida; Febri Nur Wahyudi; Jayadi Rahman (Politeknik Siber Cerdika Internasional, 2026)
Background: Digital development has transformed supply chain management (SCM) through key technologies such as the Internet of Things, artificial intelligence, blockchain, big data analytics, digital twins, and cloud computing, each providing unique contributions to operational efficiency and resilience. Despite the rapid growth of literature on digital SCM, significant gaps remain, as most studies examine technologies individually rather than exploring their combined effects on supply chain performance. Objective: This study aims to present the latest scientific literature on the use of digital technologies to improve, identify, classify, and integrate supply chain management (SCM) through a methodological literature review (SLR) approach. Methods: This study was conducted from 2021 to 2025 using databases such as Scopus, Web of Science, and Google Scholar. Of the first 309 selections, the last 10 articles met the selection criteria after progressive selection. Results: The results show that the most prominent technologies are complementary elements in the digital ecosystem, where the Internet of Things (IoT), artificial intelligence (AI), blockchain, and big data analytics are integrated. Conclusions: Digital technologies such as the Internet of Things, artificial intelligence, big data analytics, and blockchain operate synergistically to improve supply chain efficiency, transparency, and resilience. Future research is recommended to assess cross-sectoral multi-technology synergies and systematically integrate social and environmental sustainability into digital supply chain frameworks.